Analysis of The Effect of Product Quality on Consumer Satisfaction Instant Noodles - Auliaul Mafazah; Mukaram (Ebiz Prima Nusa, 2024)
Currently, instant noodle brands in the Indonesian market are growing with the emergence of new local brands that offer a variety of product innovations. Competition is occurring not only with new local brands but also with imported instant noodle brands, which are starting to appear in the Indonesian market. The intense competition that occurs makes the brand of instant noodle products must be able to provide quality products in order to be able to maintain and advance their business and provide satisfaction to consumers. As a pioneer for instant noodle products in Indonesia, it does not make Supermi the best-known and best-selling product in the Indonesian market. Consumer satisfaction is one of the important factors for a brand to be an option for consumers in choosing a product. In increasing consumer satisfaction, product quality is one of the influencing factors. This study applied a quantitative descriptive method through a purposive sampling technique and a total sample of 226 participants. The results obtained from the research show that product quality has a positive and significant influence on consumer satisfaction for Supermi products.